The Risk of Albuminuria to The Ischemic Acute Patient With or Without Metabolic Syndrome - Ana Fresia; Yuneldi Anwar (Sumatera Medical Journal, 2019)
Stroke is not only a major cause of death, but also a leading cause of disability worldwide. Metabolic syndrome is one of the predictor of stroke since it has been linked to the development of atherosclerosis that will lead to cerebrovascular event. Albuminuria is known to be an indicator of endothelial dysfunction that is a major cause of cerebrovascular disease. In this study, 50 subjects of acute ischemic stroke consist of 25 subjects of acute ischemic stroke with metabolic syndrome and 25 subjects of acute ischemic stroke without metabolic syndrome. The ischemic stroke with metabolic syndrome population is significantly associated with increased risk of albuminuria 16 times higher than the ischemic stroke without metabolic syndrome (OR = 16, IK95% 1.855 – 137.97, p=0.002).Subjects of ischemic stroke with metabolic syndrome is significantly associated with increased risk of albuminuria.